2016
DOI: 10.1159/000444577
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-Term Outcome of Intratympanic Steroid Therapy as a Salvage Treatment for Acute Low-Tone Sensorineural Hearing Loss without Episodes of Vertigo

Abstract: Objectives: To evaluate the hearing outcomes of intratympanic steroid (ITS) treatment for patients with acute low-tone sensorineural hearing loss (ALHL) after failure of initial therapy and to investigate the recurrence and progression to definite Ménière's disease (MD) during a long-term follow-up. Methods: We retrospectively reviewed the medical records of 90 patients with refractory ALHL who were followed up for at least 1 year between January 2000 and April 2014. Patients who responded poorly to initial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Corticosteroids are a commonly used treatment for SSNHL in Japan [2,14]. Recently, intratympanic steroid administration has been used for some cases [15][16][17]. In our study, most idiopathic SSNHL patients received systemic steroids as a primary treatment, whereas a combination of systemic steroids and diuretic agents was mainly used for ALHL patients.…”
Section: Discussionmentioning
confidence: 84%
“…Corticosteroids are a commonly used treatment for SSNHL in Japan [2,14]. Recently, intratympanic steroid administration has been used for some cases [15][16][17]. In our study, most idiopathic SSNHL patients received systemic steroids as a primary treatment, whereas a combination of systemic steroids and diuretic agents was mainly used for ALHL patients.…”
Section: Discussionmentioning
confidence: 84%
“…Partially consistent with our finding, a comparative study with a larger sample size reported no difference in treatment outcome between low dose steroids, high dose steroids, low dose steroids plus diuretics, and ITS plus diuretics [18]. In contrast, ITS as a salvage treatment after 2 weeks of combined steroid-diuretic treatment yields better outcome than observation or continuous diuretics treatment alone for 1-year follow-up, though final treatment outcome after 5 years was not different, irrespective of treatment strategies [19]. We did not find any beneficial effect of concurrent use of ITS; however, there is some scope to adopt ITS as a salvage treatment.…”
Section: Discussionmentioning
confidence: 57%
“…This is a limitation that hinders the interpretation and comparison of treatments used for ISSHL, including the effect of ITC as salvage treatment. Thus, the results concerning recovery in this review may generally reflect an increase in the number of Salvage corticosteroid may improve the gain in PTA (dB) Difference: MD 7.39 higher (CI 95% 0.55 higher -14.22 higher) 1 Ahn 2008, Clary 2011, Covelli 2018, Erdur 2014, Moon 2011, Morita 2016 Inconsistency: Serious. The magnitude of statistical heterogeneity was high, with I ^2: 84%.…”
Section: Discussionmentioning
confidence: 82%
“…These studies were obtained in full and read for final eligibility. Eleven studies were finally included, which comprised of four randomized controlled trials (Lee et al, 2011;Li et al, 2011;Wu et al, 2011;Xenellis et al, 2006) and seven observational studies (Ahn et al, 2008;Amarillo et al, 2019;Clary et al, 2011;Covelli et al, 2018;Erdur et al, 2014;Moon et al, 2011;Morita et al, 2016). A flowchart showing the selection of studies can be seen in Figure 1 and an overview of the included studies is found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation